2021
DOI: 10.3390/su13168875
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Mechanism of Green Human Resource Management and Corporate Social Responsibility on Organizational Sustainable Performance

Abstract: Sustainable organizational achievement of firms is the dominant approach in today’s world, with an inclination on improving profitability, social condition, and a healthy environment. Based on ability, motivation, opportunity (AMO), and stakeholder theories, this study explored the green human resource management (GHRM) and corporate social responsibility (CSR) mechanism towards sustainable performance achievement. A structured questionnaire survey from 305 samples was appropriate for the quantitative study on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 77 publications
3
29
0
Order By: Relevance
“…The results of second hypothesis test showed that new technologies directly predict 0.562 of the changes related to the implementation of green human resource management practices. The review shows that the obtained results were consistent with the research results of Zhao et al (2021) and Ojo et al (2022). This result supports the idea that automobile companies in Iran can move towards the effective implementation of green human resource management practices by benefiting from new technologies such as artificial intelligence, learning management systems (LMS), and cloud computing.…”
Section: Analysis Of Hypothesis Test Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The results of second hypothesis test showed that new technologies directly predict 0.562 of the changes related to the implementation of green human resource management practices. The review shows that the obtained results were consistent with the research results of Zhao et al (2021) and Ojo et al (2022). This result supports the idea that automobile companies in Iran can move towards the effective implementation of green human resource management practices by benefiting from new technologies such as artificial intelligence, learning management systems (LMS), and cloud computing.…”
Section: Analysis Of Hypothesis Test Resultssupporting
confidence: 81%
“…Sustainability and sustainable performance is the main issue of organizations in the 21st century (Zhao et al, 2021). On the other hand, the use of new technologies in various fields, including technology and digitalization in their nature, has caused a very dynamic environment with many changes to lead organizations to Тable 6.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the recent studies emphasizing Green human resource management include W.-K. Chen, Nalluri, Hung, Chang, and Lin (2021), which focuses on CE and environmentally friendly practices, Pham et al (2022) evaluated the implementation of GHRM and its advantages in hotels with a star rating of 4 or 5 in developing countries, Jia, Liu, Chin, and Hu (2018) Workers' pro-environmental behavior (PEB) and environmental transformational leadership (ETL) in Kazakhstan were examined to see whether there was any moderating effect of green human resource management (GHRM), Goel, Mehta, Kumar, and Castaño (2022) highlighted eleven obstacles in implementing the GHRM "strategy," ten in the area of "policies," nine in the area of "process." Eight in the area of "guideline formulation," Zhao et al (2021) investigated the mechanisms that contribute to the influence of green human resource management and corporate social responsibility on the sustainable performance of organizations.…”
Section: Green Human Resource Managementmentioning
confidence: 99%
“…The idea argues that an organization has multiple stakeholders, each of whom is impacted by the organization's success. Since stakeholders' objectives are inherently self-centred, they may have different or competing interests (Zhao et al ., 2021). The stakeholder approach indicates that stakeholders are a group or set of policies that directly or indirectly impact the operations and decisions of the company.…”
Section: Literature Reviewmentioning
confidence: 99%